Perbaikan Kondisi Kerja Serta Pemberian McKenzie exercise Dan Peregangan Statis Memperbaiki Respon Fisiologis Dan Meningkatkan Produktivitas Pekerja Pada Industri Pembuatan Dupa Di UD. Manik Galih Tabanan - Ni Luh Made Reny Wahyu Sari; Luh Made Indah Sri Handari Adiputra; I Made Muliarta; Nyoman Adiputra; I Wayan Surata; Ida Bagus Alit Swamardika (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2019)
The workers who work at incense shaping department using a chair without backrest. The container is placed below cause the worker to take it with a bent position. The table to put incense is too short, so that when held incense on the incense pads the position of workers tends to bend. These conditions cause the musculoskeletal complaints, fatigue, and increase the workload. The purpose of the study was to analyze an improved working conditions and combination of static stretching and McKenzie exercise to improve physiological response in the form of decreased musculoskeletal complaints, fatigue, and increase worker productivity. Research has been done on 10 workers working in the incense shaping department. The study was conducted in March 2018 - April 2018 held at UD. Manik Galih Tabanan. Physiology response was assessed using Nordic Body Map questionnaire 30 Items of Rating Scale. Intervention was applied in working station using chair with backrest, static exercise and McKenzie exercise. The different between Period 1 and Periode 2 were analized. The resultshowed that mean fatigue (post) at Period 1 was 55±1.49 and Period 2 was 36,8 ± 2,89, so decrease 41,48% significantly (p<0.05). The mean of musculoskeletal complaints after work in Period 1 was 73.6±4.46 and Period 2 was 43±4.53, decrease about 41.57% significantly (p<0.05). The productivity average of period 1 was 0.119 ±0.038 and period 2 was 0.198±0,055 an increase of 35.80% (p<0.05). It cloncluded that improving working condition and combination of static stretching and McKenzie exercise can decrease physiological response and increase work productivity for workers in incense shaping department at UD. Manik Galih Tabanan.